A Single Step Impression Technique of Flabby Ridges Using Monophase Polyvinylsiloxane Material: A Case Report - Umesh Y. Pai; Vikram Simha Reddy; Rushad Nariman Hosi (Hindawi Limited, 2014)
Complete denture fabrication in clinically compromised situations such as flabby ridges is a challenging task for the clinician. Accurate impressioning of these tissues plays a major role in ensuring a well-fitting prosthesis. In this paper, the authors have proposed a newer technique of impression making of the flabby tissues using a combination of readily available newer and older materials to ensure an accurate and easy impression of these tissues.